Pengaruh Positive Self-Talk Training Terhadap Peningkatan Harga Diri Santri - Athi' Linda Yani Lindayani; Arifa Retnowuni; Imroatul Mutafiah (Institut Kesehatan YARSI Mataram, 2025)
Self-esteem is a very important aspect in the process of adolescent santri self-development, because it can affect their emotional experience and psychological adjustment. For this reason, self-esteem is very dependent on the perception or mindset that is lived. Therefore, low self-esteem is influenced by the perception of an individual's assessment of himself. This mindset, which is not necessarily entirely correct, can be reconstructed to be more positive through positive self-talk so that adolescent students can have a better perception of themselves. Positive self-talk training is a process of training conversations with oneself to define feelings, judgements, and orders towards oneself and reorganise the state of self that needs to be changed. The purpose of this study was to identify the effect of Positive Self-talk Training on increasing the self-esteem of adolescent Santri in Dormitory Al_falah. The research design used is pre-experiment with experimental design one group pre-test - posttest design. Data collection was carried out through the distribution of the Roserberg Self Esteem Scale (RSES) scale, which was taken 30 respondents with purposive sampling technique. Data analysis using the Wilcoxon Test technique. Data analysis using the help of SPSS (Statistical Program For Social Service). The results of the analysis of the effect of positive self-talk training on increasing the self-esteem of adolescent students using the Wilcoxon test at post p = 0.000 (<0.05) which means that H1 is accepted which indicates that there is a significant effect on post-treatment of the effect of positive self-talk training on increasing the self-esteem of adolescent students and experiencing an increase in self-esteem as many as 27 respondents, from the results of the study respondents chose many favorable statements by feeling more valuable and more confident. ABSTRAK Harga diri merupakan aspek yang sangat penting dalam proses perkembangan diri remaja santri, karena dapat mempengaruhi pengalaman emosional dan penyesuaian psikologisnya. Untuk itu harga diri sangat bergantung pada persepsi atau pola pikir yang dijalani. Maka dari itu harga diri yang rendah dipengaruhi oleh persepsi atas penilaian individu terhadap dirinya. Pola pikir yang belum tentu sepenuhnya benar ini dapat direkonstruksi menjadi lebih positif melalui positif self-talk sehingga remaja santri dapat lebih memiliki persepsi yang lebih baik terhadap dirinya. Positive self-talk training adalah suatu proses pelatihan percakapan dengan dirinya sendiri untuk mendefinisikan perasaan, penilaian, dan perintah terhadap dirinya sendiri dan mengatur kembali keadaan diri yang perlu dirubah. Tujuan penelitian ini adalah untuk mengidentifikasi Pengaruh Positive Self-talk Training Terhadap Peningkatan Harga Diri Remaja Santri di Asrama Al-Falah. Desain penelitian yang digunakan adalah pra-eksprimen dengan rancangan eksperimen one group pre-test – posttest design. Pengumpulan data dilakukan melalui penyebaran skala Roserberg Harga Diri Scale (RSES), yang mana diambil 30 responden dengan teknik sampling purposive sampling. Analisis data menggunakan teknik Uji Wilcoxon. Analisis data dengan menggunakan bantuan SPSS (Statistical Program For Social Service). Hasil analisa pengaruh positive self-talk training terhadap peningkatan harga diri remaja santri menggunakan uji Wilcoxon pada post p = 0,000 (<0,05) yang berarti H1 diterima yang menunjukkan bahwa ada pengaruh yang signifikan terhadap post perlakuan pengaruh positive self-talk training terhadap peningkatan harga diri remaja santri dan mengalami peningkatan harga diri sebanyak 27 responden, dari hasil penelitian responden banyak memilih pernyataan favorable dengan merasa lebih berharga dan lebih percaya diri.